Platelet Count to Spleen Diameter Ratio for the Diagnosis of Esophageal Varices: Is It Feasible? - Waqas Wahid Baig; MV Nagaraja; Muralidhar Varma; Ravindra Prabhu (Canadian Journal of Gastroenterology)
AIM: To study the value of platelet count to spleen diameter ratio as a noninvasive parameter for diagnosing esophageal varices (EVs) in liver cirrhosis.